The Hawthorne School [large type] - Perry, Sylvie (Center Point Large Print, 2022)
Claudia Morgan is overwhelmed. She's a single parent trying the best that she can, but her four-year-old son, Henry, is a handful--for her and for his preschool. When Claudia hears about a school with an atypical teaching style near her Chicagoland home, she has to visit. The Hawthorne School is beautiful and has everything she dreams of for Henry: time to play outside, music, and art. The head of the school, Zelma, will even let Claudia volunteer to cover the cost of tuition.